THE PROSPECTS OF UNLIMITED CATEGORY THEORY: DOING WHAT REMAINS TO BE DONE. Issue 2 (10th February 2015) - ERNST, MICHAEL
Abstract: The big question at the end of Feferman (2013 ) is: Is it possible to find a foundation for unlimited category theory? I show that the answer is no by showing that unlimited category theory is inconsistent.